2010
DOI: 10.1111/j.1464-410x.2010.09434.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the detection of subclinical inguinal hernias in men undergoing open radical retropubic prostatectomy

Abstract: Study Type – Diagnostic (exploratory cohort)
Level of Evidence 2bOBJECTIVETo evaluate the role of magnetic resonance imaging (MRI) and up‐standing ultrasonography (USUS) for the detection of inguinal hernias (IHs) before open radical retropubic prostatectomy (ORRP) and to assess factors associated with the presence of IHs in these men.PATIENTS AND METHODSFrom 1 July 2007 to 1 February 2009, 164 men underwent preoperative evaluation for ORRP by one surgeon. Of these men 113 (69%) were evaluated for IHs by physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Even the patients without subjective symptoms had suspected IH on imaging and intraoperative findings [18,22] . In RARP cases, Lee et al [13] showed that lesser number of people, 7 groins out of 361 (1.9%) normal groins, developed IH.…”
Section: Discussionmentioning
confidence: 99%
“…Even the patients without subjective symptoms had suspected IH on imaging and intraoperative findings [18,22] . In RARP cases, Lee et al [13] showed that lesser number of people, 7 groins out of 361 (1.9%) normal groins, developed IH.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative screening for subclinical hernia and subsequent repair at prostatectomy have been suggested, 26,27 and some surgeons do in fact perform hernia repair or sutures to prevent hernia at the time of the prostatectomy. 28 However, it is unlikely that all subclinical hernias should be repaired, 29,30 because 6% of men undergoing groin hernia repair have pain that interferes with everyday life activity after surgery, 31 and far from all hernias are symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that subclinical IHs can be detected using US or MRI if special protocols are used [13]. One disadvantage of MRI is that it is performed in the supine position, which is not optimal for detecting IHs.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography of the bilateral inguinal canals was carried out as the patient was performing a Valsalva manoeuvre while in the upstanding position and was interpreted by a single experienced radiologist using a Sequoia ultrasound machine and a 10‐MHz linear transducer. An MRI of the inguinal canals was performed in the supine position at rest and during a Valsalva manoeuvre during a prostate MRI examination as previously described [13]. In less than 5% of cases the prostate MRI was performed at another institution without Valsalva.…”
Section: Methodsmentioning
confidence: 99%